Analisis Resepsi Mahasiswa Universitas Riau Terhadap Budaya Berbagi dengan Challenge Orang Pertama di Konten Tiktok @Iben M.A - Mardiana Mardiana (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study examines the reception of Riau University students regarding sharing culture with the "first person challenge" in @Iben M.A TikTok content. Using Stuart Hall's reception analysis approach with qualitative methodology, this research involved interviews with ten students from diverse faculties. The findings reveal three distinct reception positions: dominant (three informants who fully accept the content as positive sharing culture), negotiated (five informants who accept with reservations about public display of charity), and oppositional (two informants who reject the content as exploitation or virtue signaling). Reception differences were influenced by economic background, religion, parental upbringing, education, interests, and habits. Despite varying interpretations, most informants recognized the content's positive impact while expressing concerns about maintaining the essence of sharing culture in digital media representation..